2011
DOI: 10.1016/j.jhep.2010.12.017
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein levels in relation to various features of non-alcoholic fatty liver disease among obese patients

Abstract: This study indicates that it is the accumulation of fat -both in the adipose tissue and in liver steatosis- that leads to increased hs-CRP levels among obese patients. Thus, hs-CRP may be a marker of steatosis, but not of severity of NAFLD, in obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 26 publications
10
73
3
2
Order By: Relevance
“…Of these adipocytokines, leptin, adiponectin, resistin, tumor necrosis factor, and interleukin have been found to be closely related to NAFLD. In addition, hs-CRP is another important inflammatory factor and has been regarded as a pivotal factor that can predict chronic inflammatory reaction, metabolic syndrome, and cardiovascular diseases (14). Adiponectin is one of proteins with high expression in the adipose tissues, which can inhibit inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Of these adipocytokines, leptin, adiponectin, resistin, tumor necrosis factor, and interleukin have been found to be closely related to NAFLD. In addition, hs-CRP is another important inflammatory factor and has been regarded as a pivotal factor that can predict chronic inflammatory reaction, metabolic syndrome, and cardiovascular diseases (14). Adiponectin is one of proteins with high expression in the adipose tissues, which can inhibit inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role hs-CRP in differentiating severity of NASH remains controversial. Zimmermann et al [40] demonstrated a strong positive association between BMI and hs-CRP levels, which were measured with nephelometry, throughout the broad range of obesity. However, there were no significant associations between inflammation or fibrosis, respectively validation of PTX-3 is warranted to assess the usefulness of PTX-3 in understanding NAFLD.…”
Section: Acute Phase Proteinsmentioning
confidence: 99%
“…The increased production and delayed clearance of hyaluronic acid have been demonstrated to be associated with the severity of hepatic inflammation [56] . Type Ⅳ collagen is the main collagen component of basement membrane whereas laminin is the main non-collagenous glycoproand hs-CRP observed [40] . Serum haemoglobin levels have been observed to be significantly elevated in extremely obese NAFLD patient and shown to be significantly associated with prevalence of NAFLD [41][42][43] .…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…It thus appeared that it is the increased of adipocytes as liver steatosis -might lead to elevated hs-CRP levels in over-weight patients. C-reactive protein can be act as a marker of steatosis, but not in other liver disease cases (Esther et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The CRP expression in the liver more than in the adipose tissue. The total amount of hs-CRP released in the adipose tissue may be limited by the amount of adipose tissue of the human body (Esther et al, 2015).…”
Section: Resultsmentioning
confidence: 99%